Molecular Association and Hydrogen Bonding in Aqueous Uracil: A Thermo-Acoustical Approach - P. D. Bageshwar (International Journal of Scientific Research in Science and Technology, 2025)
The present study investigates the thermo-acoustical properties of aqueous uracil solutions at different molar concentrations and temperatures. Experimental measurements of density, viscosity and ultrasonic velocity were employed to evaluate several derived parameters, including adiabatic compressibility, acoustic impedance, free length, free volume and internal pressure. The variations of these parameters with molar concentration indicate strong molecular associations, primarily governed by hydrogen bonding and dipole-induced dipole interactions between uracil and water molecules. Results demonstrate that ultrasonic velocity, viscosity and acoustic impedance increase with concentration, while compressibility and free length decrease, signifying enhanced molecular interactions. The findings provide valuable insights into solute-solvent interactions, molecular association, and structural reorganization in binary liquid mixtures.